2000
DOI: 10.1164/ajrccm.162.6.2003112
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Severe, Early-Onset Chronic Obstructive Pulmonary Disease

Abstract: Men have higher prevalence rates of chronic obstructive pulmonary disease (COPD) than women, which has been attributed to the historically higher rates of cigarette smoking in males. However, the increased rates of cigarette smoking in females within the last several decades have been associated with steadily increasing rates of COPD in women. As part of a study of the genetics of severe, early-onset COPD, we assembled a group of 84 probands with severe, early-onset COPD (without severe alpha(1)-antitrypsin de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
153
1
15

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(182 citation statements)
references
References 30 publications
13
153
1
15
Order By: Relevance
“…Among the small series of patients with telomeraseassociated emphysema heretofore reported, 90% are female even though the populations studied have been equally divided between males and females (33). Interestingly, this female predominance of severe disease among telomerase mutation carriers recapitulates a pattern previously documented in a Boston-based study of familial COPD in which 80% of probands younger than 53 years were female (6,34). Importantly, the female-predominant susceptibility in telomerase mutation carriers contrasts with the predilection to disease manifesting earlier and more severely in men with alpha-1 antitrypsin deficiency (35).…”
Section: Forms Of Emphysemasupporting
confidence: 74%
“…Among the small series of patients with telomeraseassociated emphysema heretofore reported, 90% are female even though the populations studied have been equally divided between males and females (33). Interestingly, this female predominance of severe disease among telomerase mutation carriers recapitulates a pattern previously documented in a Boston-based study of familial COPD in which 80% of probands younger than 53 years were female (6,34). Importantly, the female-predominant susceptibility in telomerase mutation carriers contrasts with the predilection to disease manifesting earlier and more severely in men with alpha-1 antitrypsin deficiency (35).…”
Section: Forms Of Emphysemasupporting
confidence: 74%
“…(9,27) The changing pattern of COPD is a reflection of the increasing prevalence of smoking among women, and studies have revealed that women are more susceptible to tobacco smoke than men. (28) An estimated 210 million people worldwide are affected by COPD, and 90% of COPD deaths occur in low-or middle-income countries. (29) The COPD-related mortality rate is projected to increase by more than 30% over the next 10 years unless immediate action is taken to reduce the prevalence of underlying risk factors, especially smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there have been significantly greater rates of FEV1 decline among female smokers compared with male smokers, as shown in an epidemiological setting in the Netherlands [54]. Finally, a sex difference in severe, earlyonset COPD has been demonstrated [55]. In the offspring of 84 individuals with severe, early-onset COPD, there was a markedly elevated prevalence (71.4%) in females.…”
Section: Sex and Sex Differencesmentioning
confidence: 97%